Investigating the osteogenic potential of multipotent mesenchymal stromal cells through the use of DNA microarray technology and biomaterial nanotopography - Berger, Dustin, author; Prasad, Ashok, advisor; Popat, Ketul, advisor; DeLuca, Jennifer, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: osteogenesis; differentiation; mesenchymal stem cell; microarray; nanotopography